(untitled) (Research, Society and Development, 2023)
Objective: The objective of the study is to analyze the intervention of supervised physical exercises in middle-aged adults with post-COVID-19 conditions. Methodology: This is an integrative literature review, carried out by searching for studies in three national and international databases: Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (BDENF) and Medical Literature Analysis and Retrieval System Online (MEDLINE). The final sample consisted of 5 published studies. Results and Discussion: After crossing the descriptors and applicability of the inclusion and exclusion criteria, the discussion was carried out based on 5 articles. Conclusion: it is concluded that supervised physical exercise intervention is a promising approach for middle-aged adults with post-COVID-19 conditions. It aims to restore health and functionality, improve quality of life and reduce the impact of persistent symptoms. This approach, updated by research and clinical practice, represents an important step in the recovery and rehabilitation of patients facing health challenges following coronavirus infection.